Developing Speaking Board Game of Descriptive Text at MAN 1 Medan - Ade Hamka (Universitas Negeri Medan, 2021)
Developing Speaking Board Game of Descriptive Text at MAN 1 Medan Hamka Ade1 1Pendidikan Bahasa Inggris Universitas Negeri Medan Medan, Indonesia 1 adehamka98@gmail.com Abstract The aim of this study is to develop a learning media on teaching Descriptive Text at MAN 1 Medan. This study was conducted by Research & Development (R&D) design. The source of the data are the students of MAN 1 Medan which consists of thirty two students. To collect the data, the online questionnaires to the students of MAN 1 Medan was shared to obtain the students’ needs of learning media of descriptive text in the classroom and conducted an interview with the classroom teacher. There are some steps should be done to develop a learning media: Evaluation and Needs Analysis, Learning Media Design, Learning Media Development, Validation by Experts, Revision and Final Product. After doing the Evaluation and Needs Analysis, it is found that the existing learning media used in the classroom to teach Descriptive Text is not interesting for most students and unable to enhance their ability especially in Speaking skills. It can be shown from the result of the questionnaire that 87.5 % of students need a learning media to help them in improving their ability in English especially in descriptive text topic, and 46.9 % of students prefer Speaking Board Game as their learning media. The product has been validated by the experts namely English lecturer and English teacher. The product result was Speaking Board Game which is modifying Snake and Ladder game that is acclimated with the basic competence of K13. The result of experts’ validation showed that the media was an appropriate media to be used on speaking descriptive text by obtaining the average percentage 95.1% or categorized as excellent. Key words : Research and Development, Learning Media, Descriptive Text, Speaking Board Game